Clinical review: traumatic brain injury in patients receiving antiplatelet medication - Beynon, Christopher; Hertle, Daniel; Unterberg, Andreas; Sakowitz, Oliver (Critical care, 2012)
As the population ages, emergency physicians are confronted with a growing number of trauma patients receiving antithrombotic and antiplatelet medication prior to injury. In cases of traumatic brain injury, pre-injury treatment with anticoagulants has been associated with an increased risk of posttraumatic intracranial haemorrhage. Since high age itself is a well-recognised risk factor in traumatic brain injury, this population is at special risk for increased morbidity and mortality. The effects of antiplatelet medication on coagulation pathways in posttraumatic intracranial haemorrhage are not well understood, but available data suggest that the use of these agents increases the risk of an unfavourable outcome, especially in cases of severe traumatic brain injury. Standard laboratory investigations are insufficient to evaluate platelet activity, but new assays for monitoring platelet activity have been developed. Commonly used interventions to restore platelet activity include platelet transfusion and application of haemostatic drugs. Nevertheless, controlled clinical trials have not been carried out and, therefore, clinical practice guidelines are not available. In addition to the risks of the acute trauma, patients are at risk for cardiac events such as life-threatening stent thrombosis if antiplatelet therapy is withdrawn. In this review article, we summarize the pathophysiologic mechanisms of the most commonly used antiplatelet agents and analyse results of studies on the effects of this treatment on patients with traumatic brain injury. Additionally, we focus on opportunities to counteract antiplatelet effects in those patients as well as on considerations regarding the withdrawal of antiplatelet therapy. In those chronically ill patients, an interdisciplinary approach involving intensivists, neurosurgeons as well as cardiologists is often mandatory.